Factors of Purchasing Decisions of Consumers of Blukid Residence 3 Housing in Sidoarjo - Regina Ayu Kusuma Wardani (Universitas Ciputra Surabaya, 2022)
This study aims to find out and analyze what factors consumers consider in making the decision to buy a house in Blukid Residence 3 Housing. The object studied in the study was Blukid Residence 3 Housing located in the city of Sidoarjo, East Java. In 2019 marketing experienced a decline in interest in site visits, resulting in a decline in sales in our housing. The method used in this study is a quantitative method. Researchers used Confirmatory Factor Analysis (CFA) to analyze the data. This research was conducted at Blukid Residence 3 Housing located in Sidoarjo with a sample of 97 respondents.